Bi2MoO6 hierarchical hollow microspheres with remarkable electrochemical performance. Issue 18 (15th September 2022) - Cheng, Cuixia; Chen, Fang; Cheng, Yinfang; Lai, Guosong
Abstract: Hierarchical hollow architectures have demonstrated a remarkable electrochemical performance. In this contribution, Bi2 MoO6 hierarchical hollow microspheres constructed by nanosheets are prepared by a facile hydrothermal method without any post-treatment, and investigated firstly as anode of lithium-ion batteries. The time-dependent experiments show the morphology evolution from solid microspheres to hierarchical hollow microspheres. Compared with the previous reports, the results manifest expectedly a superior lithium storage performance in terms of specific capacity, cycling stability, rate capability, active energy and Li + diffusion kinetics.